Comparative Outcomes of Intravenous Hydrocortisone Versus Dexamethasone in Pediatric Patients Presenting with Croup - Nadia Hassan, Anam Raheel, Asia Shafiq, Asma Nazar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Croup is a common upper respiratory illness in children, characterized by stridor, barking cough, and respiratory distress due to subglottic airway inflammation. Corticosteroids are the mainstay of treatment in moderate to severe cases. Objective: To compare the clinical outcomes of intravenous hydrocortisone versus intravenous dexamethasone in pediatric patients presenting with moderate to severe croup. Methods: This comparative observational study was conducted at Mayo Hospital Lahore from Jan 2023 to June 2023. A total of 215 pediatric patients presenting with clinical features consistent with croup were enrolled in the study. Children aged 6 months to 6 years with a clinical diagnosis of moderate to severe croup based on the Westley croup score were included in the study. Patients with known hypersensitivity to corticosteroids, pre-existing chronic respiratory illnesses (e.g., asthma, tracheomalacia), or concurrent bacterial infections requiring antibiotics were excluded from the study. Results: Out of 215 patients, 108 received hydrocortisone and 107 received dexamethasone. The mean time to stridor resolution was significantly shorter in the dexamethasone group (12.7 ± 3.8 hours) compared to the hydrocortisone group (18.4 ± 4.3 hours; p < 0.001). Fewer patients in the dexamethasone group required ≥2 doses of nebulized epinephrine (23.4% vs. 48.1%; p = 0.001). Mean hospital stay was also shorter in the dexamethasone group (2.2 ± 0.5 days) than in the hydrocortisone group (2.9 ± 0.7 days; p < 0.001). ICU admissions were lower in the dexamethasone group (3.7%) compared to the hydrocortisone group (10.2%; p = 0.048). Conclusion: It is concluded that intravenous dexamethasone is superior to hydrocortisone in achieving faster symptom resolution, reducing hospital stays, and minimizing the need for additional interventions in pediatric patients with croup. Keywords: Croup, Patients, Efficacy, Outcomes, Edema